Comparison of BRICS-TM Countries' Biosimilar Regulatory Frameworks With Australia, Canada and Switzerland: Benchmarking Best Practices - Rahalkar, Hasumati; Sheppard, Alan; Salek, Sam (Frontiers in Pharmacology, 2021)
Objectives: The aim of this study was to identify, compare and evaluate regulatory requirements for the biosimilar development and review processes in BRICS-TM (Brazil, Russia, India, China, South Africa, Turkey, Mexico) countries with mature regulatory systems of Australia, Canada, Singapore and Switzerland. It is hoped that this benchmark study provides an opportunity for BRICS-TM agencies to identify the key areas for improvement in their regulatory processes. Materials and Methods: A semi-quantitative questionnaire was developed covering the different criteria used in biosimilar development and registration process. Eleven regulatory agencies from BRICS-TM and ACSS (Australia, Canada, Switzerland and Singapore) countries were invited to take part in this study. Data processing and analysis was carried out using descriptive statistics for quantitative data and content analysis to generate themes for qualitative data. Results and Discussions: Nine of the 11 regulatory agencies recruited for the study completed the questionnaire. China and Singapore did not meet the deadline due to lack of resources. The organisational structure of BRICS-TM agencies revealed support from external assessors by most of these agencies in comparison with ACSS agencies. There was absence of reliance approach and participation in harmonisation activities across most BRICS-TM agencies. Despite alignment over biosimilarity, the mandate for in vivo non-clinical studies and additional local clinical studies in some of the BRICS-TM countries illustrates a lack of effective implementation of a step-wise approach. Adopting flexible regulatory standards in the sourcing of a RBP (Reference Biologic Product) by BRICS-TM similar to ACSS, will facilitate cost-effective development of biosimilar products. Conclusions: Comparative assessment of the biosimilar regulatory framework of BRICS-TM with ACSS agencies reveals the scope for enhancing efficiency of the regulatory approval process. To achieve this, BRICS-TM agencies should consider relying on reference agencies for alternative review mechanisms such as abridged or verification models, streamlined processes for providing scientific advice to developers and for waiving local clinical studies in-lieu of advanced scientific data.